Multispatial scale effects of landscape patterns on seasonal water quality in Jiangnan water town under the green and integrated ecological development of the Yangtze River Delta - Ming Zhang; Hao-Rui Li; Yaoyao Fang; Xiaomian Zhang; Xiaojie Yan; Chunlei Yue; Liang-Jie Wang (Journal of Hydrology: Regional Studies)
Study region: Jiashan County, Zhejiang Province, a typical Jiangnan water town. Study focus: This study examined five water quality indices, namely pH, total nitrogen, total phosphorus, ammonia nitrogen, and the permanganate index, assessed landscape patterns at different riparian buffer scales, quantified the impacts of landscape patterns on water quality at different seasonal and spatial scales, and predicted the response of water quality under different landscape scenarios. New hydrological insights for the region: The results revealed that landscape patterns generally explained more water quality changes in the dry season than in the wet season, although this difference was relatively limited. The 800 m scale had the most significant explanatory power, ranging from 1.38 % to 35.94 % higher than that of the other scales. The total nitrogen concentration did not meet the standard under any of the different scenarios. In the future, the focus should be on monitoring total nitrogen, and the landscape is recommended to reduce fragmentation of cropland and forest land. This study provides information to support the management of riparian zone landscapes and water ecosystems, and promotes the construction of a green ecological integration demonstration area in the Yangtze River Delta.